ISOLATION AND IDENTIFICATION OF AFLATOXIN B1 PRODUCING FUNGI FROM STORED WHEAT IN SOME SILOS OF BAGHDAD - M. , Mohamed A.; Al – Shamary , E. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aim of this study was isolation and identification of  fungi producing aflatoxin B1 from wheat which was stored for four months in some silos in Baghdad , including Al Taji Silo, Khan Bani Saad Silo and Khan Dhari Silo. Those Silos were included in the  agricultural plan for the marketing season 2020. Different  types of fungi were obtained. They were initially identified according to cultural and morphological characteristics as Alternaria spp,  Aspergillus flavus , Aspergillus niger. The ability of fungal isolates to produced aflatoxin was tested using ammonia vapor. All of the Aspergillus flavus isolates showed their ability to produce aflatoxin, unlike the other types which showed negative result. Aflatoxin produced by Aspergillus flavus was estimated using (HPLC) technique, and results showed that the highest concentration (978.5 µg / ml)  was obtained from an  isolate  in Al-Taji Silo. This isolate was  genetically identified by genetic analysis of  5.8S rRNA gene. Gene  sequencing identity of local isolate was 99% in compassion to sequencing of Aspergillus flavus strain USMG09 recorded in the gene bank as ID: MK992254.1 .